Secondary metabolites, mycotoxins and mycobiomes from Nepalese field maize and soil - Shrestha, Inisa (My University, 2026)
Complex fungal communities (a.k.a. mycobiomes) can be found in maize ears. The origin of these mycobiome is not well understood. It could originate from spores in the soil, be transported by the air or rain; or be carried by insects or contaminated seeds, and its composition could be important in determining the secondary metabolites produced. A detailed understanding of the fungal community in maize seed and its influence on the secondary metabolites present remains unknown. I evaluated the mycobiomes in maize ears and the soil in which the plants were growing using ITS metabarcoding across 12 fields of two districts in Nepal with the goal of determining the contribution of the soil mycobiome to the mycobiome of the maize ear. The working hypothesis was that maize ears and soil harbor overlapping mycobiomes, but that these mycobiomes also differed by geographic location. In addition, we analyzed secondary metabolites with Liquid Chromatography-Mass Spectroscopy (LC/MS/MS) and coupled the chemical analysis with the mycobiome evaluation to assess the relationship between the maize ear mycobiomes and the secondary metabolites and mycotoxins present. The hypothesis was that the metabolites present, and their quantities, varied with the composition of the mycobiome. MiSeq ITS2 metabarcode data from the fungal communities indicated that mycobiomes from maize ears and soil were distinct as were mycobiomes from different locations, with mycobiomes of soil much larger, in terms of number of genera represented, than those from maize ears. Genera found frequently in maize were less frequent in the soil. Fusarium was usually the dominant genus from both the grain and the soil at all locations. Fungal richness and diversity were greater in soil than in the maize ears. Secondary metabolite profiles and mycobiome profiles did not always align 1:1. Aflatoxins, ochratoxin and Aspergillus spp. were recovered from only two ears. Fumonisins were recovered from 10/12 ears. A toxin-producing genus could be present even if the toxins associated with the genus were not detected. In conclusion, maize ear mycobiomes play an important role in determining the secondary metabolites present. As members of the soil and maize ear mycobiomes were distinct and even the OTUs were in common often varied widely in relative frequency, soil is unlikely the sole source of the maize ear mycobiomes.
Keywords: Aflatoxins, Fumonisins, Aspergillus, Fusarium, Penicillium and metabarcodes.